Fabrication of hydroxyapatite reinforced polymeric hydrogel membrane for regeneration - Akansha Kishen; Anju Cecil; S Chitra (Elsevier, 2023)
Background: The regeneration of lost/damaged support tissue in the periodontium, including the alveolar bone, periodontal ligament, and cementum, is an ambitious purpose of periodontal regenerative therapy and might effectively reduce periodontitis-caused tooth loss. Guided tissue regeneration (GTR) is a technique currently used in dentistry for periodontal surgery, which allows osseous regeneration prior to soft tissue migration into the area of interest. Calcium phosphate-based bone grafts (mostly Tricalcium Phosphate or Hydroxyapatite) are bio ceramics that show the greatest similarity to the mineral found in the bone. Thereby, giving calcium-phosphate excellent biocompatibility, biodegradability and osteoconductivity. The aim of the study is to fabricate hydroxyapatite reinforced polymeric hydrogel membrane for regeneration. Materials and Method: Pure alginate fabrication was done by cross linking sodium alginate with calcium chloride. Hydroxyapatite (HAP) alginate (Alg) was formulated by adding nanoparticles to the alginate mixture, which was then cross-linked with calcium chloride to formulate a HAP alginate polymeric membrane. The Fourier-transform infrared spectroscopy (FT-IR), Scanning Electron Microscope (SEM), and biocompatibility tests were performed to analyse the membrane characteristics. Results: Fabricated Hydroxyapatite- alginate (Hap- Alg) membrane has longer durability, because of strong crystal structure which in turn might take a longer time to regenerate. The membrane was found to be biocompatible and HAp induces faster mineralisation which in turn will increase the tissue regeneration rate of the membrane. Conclusion: The findings of our study suggests that the HAP-Alg hydro gel membrane is highly durable and hemocompatible and it has faster mineralisation capability thus making it superior from the clinically available membranes for GTR. Further analyses needs to be conducted to evaluate the potential of this membrane to be used for regeneration.